2021
DOI: 10.1002/cpt.2187
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of HIV Cure: Site of Action

Abstract: Despite significant advances in HIV treatment over the past 30 years, critical barriers to an HIV cure persist. The HIV reservoir, defined at both the cellular and anatomical level, constitutes the main barrier to cure. While the mechanisms underlying the reservoir are not yet well understood, one theory to explain persistence at the anatomical level is that subtherapeutic exposure to antiretroviral therapy (ART) within certain tissue compartments permits ongoing replication. Characterizing ART pharmacology th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 110 publications
(264 reference statements)
0
7
0
Order By: Relevance
“…They determined that in lymph nodes with diameters less than 0.1 mm (which translates to an absence of inflammation) there is no persistent viral replication despite low drug levels, although the chances of replication increase as the node size increases. Protease inhibitors [ 117 , 118 ] are the therapeutic group that diffuses the worst in this tissue, and regimens based on these drugs are the ones that could be most associated with the establishment of drug sanctuaries [ 116 ]. Tenofovir disoproxil difumarate, emtricitabine, atazanavir, darunavir and efavirenz also have poor activity in lymphoid tissue [ 112 , 118 ], as well as integrase inhibitors [ 118 , 119 , 120 , 121 ].…”
Section: Persistent Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…They determined that in lymph nodes with diameters less than 0.1 mm (which translates to an absence of inflammation) there is no persistent viral replication despite low drug levels, although the chances of replication increase as the node size increases. Protease inhibitors [ 117 , 118 ] are the therapeutic group that diffuses the worst in this tissue, and regimens based on these drugs are the ones that could be most associated with the establishment of drug sanctuaries [ 116 ]. Tenofovir disoproxil difumarate, emtricitabine, atazanavir, darunavir and efavirenz also have poor activity in lymphoid tissue [ 112 , 118 ], as well as integrase inhibitors [ 118 , 119 , 120 , 121 ].…”
Section: Persistent Viral Replicationmentioning
confidence: 99%
“…Protease inhibitors [ 117 , 118 ] are the therapeutic group that diffuses the worst in this tissue, and regimens based on these drugs are the ones that could be most associated with the establishment of drug sanctuaries [ 116 ]. Tenofovir disoproxil difumarate, emtricitabine, atazanavir, darunavir and efavirenz also have poor activity in lymphoid tissue [ 112 , 118 ], as well as integrase inhibitors [ 118 , 119 , 120 , 121 ]. However, there is recent evidence supporting the better diffusion of tenofovir alafenamide at the lymph node level, which would be an theoretical advantage when using these drugs [ 122 ] ( Table 1 ).…”
Section: Persistent Viral Replicationmentioning
confidence: 99%
“…3233 Additionally, strategies to cure HIV are complicated in part by pharmacological challenges (eg, limited drug distribution at effector sites such as in tissues, inadequate therapeutic efficacy, and unfavorable drug toxicity). 3435…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of antiretroviral pharmacokinetics in the female genital tract (FGT) is of growing interest in the HIV prevention field because of its importance in designing more effective therapeutic options to reduce serodiscordant and mother-to-child HIV transmission [1]. Although a number of clinical studies that focus on quantifying antiretroviral drugs in the FGT have been reported in the literature [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%